2020
DOI: 10.1101/2020.06.09.142612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating daily intakes of manganese due to breast milk, infant formulas, or young child nutritional beverages in the United States and France: Comparison to sufficiency and toxicity thresholds

Abstract: Laboratories provided no input in choosing the subject matter of this project, the hypotheses that were tested, the method of analysis, the research findings, the decision to publish, or the manner of disseminating the results. This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Highlights1. Mn deficiency is unlikely with exclusive breast milk or infant formula feeding.2. Breast milk Mn mean intake is 1.2 µg/kg/day (3 weeks)-0.16 µg/kg/da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 89 publications
(111 reference statements)
0
2
1
Order By: Relevance
“…However, Cr levels in breast milk reported from Iran were much higher than in the present study, with median levels of 3.95 µg/L, and these levels were attributed to exposure through contaminated foodstuff [ 13 ]. The median Mn levels from breast milk were significantly lower ( p < 0.05) than those reported in literature, with most other studies reporting values ≥ 1 µg/L [ 35 , 55 , 56 , 57 , 58 ]. A study by Mitchell et al (2020) summarized the levels of Mn in breast milk reported in more than 20 different countries from January 1980 to December 2017.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…However, Cr levels in breast milk reported from Iran were much higher than in the present study, with median levels of 3.95 µg/L, and these levels were attributed to exposure through contaminated foodstuff [ 13 ]. The median Mn levels from breast milk were significantly lower ( p < 0.05) than those reported in literature, with most other studies reporting values ≥ 1 µg/L [ 35 , 55 , 56 , 57 , 58 ]. A study by Mitchell et al (2020) summarized the levels of Mn in breast milk reported in more than 20 different countries from January 1980 to December 2017.…”
Section: Resultscontrasting
confidence: 60%
“…A study by Mitchell et al (2020) summarized the levels of Mn in breast milk reported in more than 20 different countries from January 1980 to December 2017. From this summary, levels of Mn in 5 423 breast milk samples ranged from 0.17 to 30.27 µg/L, and a mean of means of 7.7 µg/L was established [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation